Theoretical and experimental aspects of electrodeposition under hydrodynamic conditions - Hyde, M; Compton, R (2005)
The utility of a recently derived model [M.E. Hyde, O.V. Klymenko, R.G. Compton, J. Electroanal. Chem. 534 (2002) 13] for the potentiostatic nucleation and three dimensional growth of deposits on an electrode surface under hydrodynamic conditions is demonstrated. 2.1 mM Pb2+ solution is used as the depositing species, and a wall-tube and stirred cell are used to generate conditions in which the diffusion layer thickness is in the range 10-40 μm. It is shown that the model provides excellent fits to the experimental data. The nucleation parameters N0, the number of active sites, and A, the nucleation rate are derived from analysis of the transients. These values are compared to those extracted from experiments under quiescent conditions, and also to previously reported data in which ultrasound was used to induce hydrodynamic flow. © 2005 Elsevier B.V. All rights reserved.